2018
DOI: 10.1007/s40571-018-0210-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of geometry and fill level on the transport and mixing behaviour of a co-rotating twin screw extruder

Abstract: The transport and mixing properties of a co-rotating twin screw extruder with both screw elements and kneading blocks are explored using the Smoothed Particle Hydrodynamics (SPH) method. The use of a Lagrangian method enables simulation of extruders partially or fully filled with fluid and is not limited by problems associated with extreme mesh deformation due to the opposite rotation of the impellors or the small gaps between them.The cross-channel and axial fluid transport and mixing in the screw elements an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Taki et al [ 18 ] found that the degree of fill was inversely proportional to the rotational speed and proportional to the feed rate. Robinson and Cleary [ 19 ] studied the effect of degree of fill on the transport and mixing behavior of a corotating TSE and found that a fill level of 50% produces the highest mixing rates for the screw elements. The degree of fill for the OSE was determined.…”
Section: Resultsmentioning
confidence: 99%
“…Taki et al [ 18 ] found that the degree of fill was inversely proportional to the rotational speed and proportional to the feed rate. Robinson and Cleary [ 19 ] studied the effect of degree of fill on the transport and mixing behavior of a corotating TSE and found that a fill level of 50% produces the highest mixing rates for the screw elements. The degree of fill for the OSE was determined.…”
Section: Resultsmentioning
confidence: 99%
“…Our approach uses smoothed particle hydrodynamics (SPH), a relatively new numerical method for simulating complex free surface flows occurring inside the rotating screws. SPH is a Lagrangian-based fluid dynamics model, with the fluid flow represented as a continuum of moving fluid parcels that can adjust naturally to the complex intermeshing movement of twin screw extruders without a numerical mesh (88)(89)(90)(91)(92)(93)(94)(95). The Lagrangian nature of the method also allows for a straightforward investigation of the flow in partially filled screw elements, as well as, a detailed investigation of the distributive mixing action of the screw geometry selected.…”
Section: Process Development and Control Process Setup And Scale-up Vmentioning
confidence: 99%
“…Full 3D results have been obtained using commercial software like POLYFLOW which is based on a mesh superposition method that avoids re-meshing [3,4]. A rather recent development are methods using smoothed particle hydrodynamics [5,6]. These methods are extremely useful in case only partly filled extruders are considered.…”
Section: Introductionmentioning
confidence: 99%